Adult Flexible Flatfoot Due to Insufficiency of Posterior Tibial Tendon: Calcaneo-Stop and Tensioning of PTT in Grade IIA. Issue 1 (19th August 2016) - Ceccarini, Paolo; Rinonapoli, Giuseppe; Gambaracci, Giulio; Bisaccia, Michele; Ceccarini, Alfredo; Caraffa, Auro
Category: Hindfoot Introduction/Purpose: We postulated that in a flexible adult flatfoot, calcaneo-stop procedure combined with medial tensioning of posterior tibial tendon allowed the resolution of symptoms by correcting the pattern of the gait and avoiding the evolution to a subsequent stage. The purpose of this study was to determine functional, biomechanic, and radiographic results in patients who underwent surgery for flexible flatfoot without osteotomies or arthrodesis. Methods: We evaluated clinically and radiographically 29 patients surgically treated for adult flatfoot grade IIa according to Myerson, with a mean age of 46.4 years. Mean follow-up was 34.15 months. For clinical evaluation the AOFAS hindfoot and VAS- FA scores were used. In 10 patients, pre and post-operatively gait analisys was performed. Results: Postoperative results showed a significant increase of AOFAS and VAS-FA scores, from 54.7 (range 34 to 78) to 83.1 (range 66-100) and 60.5 (range 35-86) 85 (range 64-100) points, respectively. For the X-ray parameters, in the AP projection, we observed a significant variation of Kite's angle, from 24.2° in the pre-op to 19.2° in the post-op. In lateral view Costa-Bertani angle showed changes from 146.8° to 140.5°. The Meary's angle, showed an average at the post-op of 4.3°. Postoperative satisfaction was excellent-good for 25 patients (86.2%). Postoperative gait analysis showed an improved pattern of the gait. Conclusion: The technique of arthroereisis with medial tensioning of PTT is a valid technique for the young adult, up to 50 years and with no signs of osteoarthritis of the midfoot and hindfoot.